Adsorption-rheological properties of blood serum in lung cancer patients - Dumanskiy, Y.V.; Stoliarova, O.Y.; Syniachenko, O.V.; Giulmamedova, M.F.; Potapov, Y.A. (Experimental Oncology, 2017)
The aim and objectives of the study were to investigate the state of adsorption-rheological properties of blood (ARPB) in patients with different clinical course of lung cancer (LC), the detection of violations of surface-active, viscoelastic and relaxation properties of blood serum, their association with tumor markers, the evaluation of the prognostic value of initial indexes in the development of complications from radiochemotherapy. Patients and Methods: The study included 115 patients with LC at the age from 24 to 80 years (average age 58 years), among whom there were 78% men and 22% women. The parameters of surface (interfacial) viscosity, elasticity, viscoelasticity module, tension and relaxation of blood serum were studied by the oscillating drop method using a computer tensiometer “PAT2-Sinterface”, and its volumetric viscosity was investigated using a Low-Shear-30 rotational viscometer. ARPB parameters were also studied in a control group composed from 50 healthy donors. Results: Increased levels of volumetrical viscosity, surface tension, surface elasticity and the relaxation time of the blood are typical for patients with LC and depended on the localization of the tumor, its histological variant, differentiation grade, severity of the course of the disease, the number of metastases in the lymph nodes, distant organs and skeleton, involvement of the pleura and ribs, the development of compression pulmonary syndrome, metastasis into the spine, adrenals, brain, and pancreas. The surface-active, viscoelastic and relaxation properties of the blood correlated with the levels of tumor markers (TGFβ1, VEGF, C-reactive protein, α2-macroglobulin). Conclusions: Integral changes of ARPB observed in every fifth patient with LC are involved in the pathogenesis of the disease, have predictive value in relation to the clinical course of disease (volumetric viscosity) and the development of complications from radiochemotherapy (surface viscosity).